Dolastatin 15 from a Marine Cyanobacterium Suppresses HIF‐1α Mediated Cancer Cell Viability and Vascularization. (12th May 2020) - Ratnayake, Ranjala; Gunasekera, Sarath P.; Ma, Jia Jia; Dang, Long H.; Carney, Thomas J.; Paul, Valerie J.; Luesch, Hendrik
Abstract: Chemical investigation of a benthic marine cyanobacterium yielded the anticancer agent dolastatin 15, originally isolated from a mollusk. Dolastatin 15 is a microtubule‐destabilizing agent with analogues undergoing clinical evaluation. Profiling against a panel of isogenic HCT116 colorectal cancer cells showed remarkable differential cytotoxicity against the parental cells over isogenic cells lacking HIF or other key players in the pathway, including oncogenic KRAS and VEGF. Dolastatin 15 displayed an antivascularization effect in human endothelial cells and in zebrafish vhl mutants with activated Hif, thus signifying its clinical potential as a treatment for solid tumors with an angiogenic component. Global transcriptome analysis with RNA sequencing suggested that dolastatin 15 could affect other major cancer pathways that might not directly involve tubulin or HIF. The identification of the true producer of a clinically relevant agent is important for sustainable supply, as is understanding the biosynthesis, and future genetic manipulation of the biosynthetic gene cluster for analogue production. Abstract : The true producer of the clinically relevant microtubule‐destabilizing agent dolastatin 15 has been determined. Isogenic cell‐line screening indicated that its cytotoxicity is mediated by HIF‐1α, controlling angiogenesis. Dolastatin 15 inhibited vascularization in cell and zebrafish models, thus suggesting its potential to treat vascularized tumors. RNA‐seq provided a global snapshot of the anticancer effects.